(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Interpretation plays a vital role in the comprehension and appreciation of literary texts. It involves analyzing and uncovering meanings, themes, and connections that may not be immediately evident. Since literature is often layered with ambiguity, symbolism, and cultural context, interpretation is essential to bridge the gap between the author’s intent and the reader’s understanding.This article gives information about the role of imagination and interpretation of literary text.